IoT Based Monitoring System for Fresh Fruit Bunch (FFB) Quality Indicators Using TCS3200 Color Sensor and LoRa Communication at the Palm Oil Mill Receiving Process - Nabil Azzaidan Nasution; Ratu Mutiara Siregar; Muhammad Akbar Syahbana Pane (Sisfo: Jurnal Ilmiah Sistem Informasi, 2026)
Abstract The quality of Fresh Fruit Bunches (FFB) has a substantial impact on the efficiency of palm oil processing. Nevertheless, traditional assessment techniques remain manual and subjective. This research introduces an Internet of Things (IoT)-based monitoring system designed for the real-time and objective evaluation of FFB maturity. The system employs a TCS3200 color sensor alongside a DHT22 sensor, which are integrated with an ESP32 microcontroller and utilize LoRa communication for long-distance data transmission. The data collected is sent to the ThingSpeak platform for real-time visualization.Field trials conducted at the Cinta Raja plantation indicate that the system is capable of categorizing FFB maturity into ripe, unripe, and undetected based on the predominant color components. However, its performance is affected by environmental variables, especially lighting conditions.In summary, the system offers a practical and cost-effective solution for monitoring FFB quality, although further enhancements in calibration and environmental control are necessary to improve accuracy and reliability.